2020
DOI: 10.3390/ijerph17249298
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and Barriers for the Use of Face Coverings during the COVID-19 Pandemic: Messaging Insights from Focus Groups

Abstract: Widespread use of face coverings is a key public health strategy to prevent the spread of COVID-19. However, few studies have examined why Americans use or do not use face coverings, and little is known about the most effective messaging strategies. This study explored perceptions of face coverings, including motivations and barriers for use, and examined reactions to messaging promoting the use of face coverings. Six virtual focus groups were conducted with 34 North Carolina residents in July 2020. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 26 publications
7
68
1
Order By: Relevance
“…A study done with healthcare workers demonstrated a positive attitude but there was a moderate-to-poor level of knowledge and practice regarding the use of face masks. Therefore, it has been recommended that healthcare worker and general public awareness campaigns be conducted concerning the appropriate use of face masks by using the available social media resources which would be especially helpful during the pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study done with healthcare workers demonstrated a positive attitude but there was a moderate-to-poor level of knowledge and practice regarding the use of face masks. Therefore, it has been recommended that healthcare worker and general public awareness campaigns be conducted concerning the appropriate use of face masks by using the available social media resources which would be especially helpful during the pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the community’s compliance in wearing face masks requires information about their knowledge, attitudes, and perceptions, and then, identification and assessment of the barriers preventing compliance. Physical and social discomfort, confusion or misinformation, low perceived susceptibility to COVID-19, and perceptions of identity and autonomy were reported as the main barriers in using face masks [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Statements were rooted in Health Belief Model constructs of perceived benefit, susceptibility, severity, barriers, and self-efficacy [ 14 , 19 ]. Participants were asked “How much do these reasons make you want to wear a face covering?” followed by a randomized list of 18 statements informed by qualitative work (see Table 2 for a complete list of the statements) [ 20 ]. Example statements included “Wearing a face covering could prevent me from getting COVID-19” and “I want to protect people who are vulnerable”.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies in the US have reported that male, younger age, race/ethnicity (i.e., being white compared to being black or Hispanic), political party (i.e., being a Republican), and living in rural areas were risk factors for not wearing a face mask [ 6 , 8 , 9 ]. A qualitative research in the US also found that barriers included discomfort associated with the use, misinformation, perceived low susceptibility, and perceptions of autonomy [ 10 ]. Interestingly, this study [ 10 ] and another one that was also conducted in the US [ 11 ] found that perceptions and the influence of people around them were one of the major determinants related to mask use.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative research in the US also found that barriers included discomfort associated with the use, misinformation, perceived low susceptibility, and perceptions of autonomy [ 10 ]. Interestingly, this study [ 10 ] and another one that was also conducted in the US [ 11 ] found that perceptions and the influence of people around them were one of the major determinants related to mask use. For example, the qualitative study reported that the major motivation for the use of face covering was protect or respect for other people [ 10 ].…”
Section: Introductionmentioning
confidence: 99%